تأثير استخدام وسيلة صندوق القراءة على مهارة القراءة الطّلّاب بمدرسة الثّانويّة الحكوميّة ۲ بادنج بنجانج - Rahmadani, Nurul; Febrianta, Rita; Anas, Al Baihaqi; Yusra, Oktarina (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
There are several problems in learning Arabic, namely the teacher does not use different learning media in teaching, especially in reading skills. It will be more interesting if the teacher is creative in using different media, so that it can increase students' enthusiasm and motivate them in learning. The problem is, teachers still have difficulty developing many Arabic learning media that suit the needs of students. The researcher decided to examine the effect of reading box media (a different method than usual) on students' reading abilities. Researchers use experimental research methods because researchers will look for the effect of certain treatments on others in the subjects held. This means looking for the effect of using reading box media on students' reading skills. The number of the research community consisted of 17 students, and the researchers took a random sample in this thesis, namely 17 students. Then the research instrument is observation, test. The researcher used reading box media in the experimental class to understand the text of reading skills in eleventh grade Arabic lessons well and fluently with an average score of 87.76, and in the control class with an average score of 80.06. . The result of calculating T (2.263) is greater than T table (2.037). The researcher concludes that the null hypothesis is rejected and the alternative hypothesis is accepted.